Islamic Social Finance and Endogenous Growth: The Contribution of Zakat and Waqf to Poverty Alleviation in Indonesia - Siti Aminah Najmudin; Sayyid Shadiq; Yogi Kurniawan (Journal of Social Entrepreneurship Theory and Practice, 2026)
In Indonesia, Islamic social finance, anchored by the instruments of zakat and waqf, plays a crucial role in poverty alleviation and the promotion of inclusive growth. Despite this, its full potential as a driver of long-term development remains underexplored, particularly its connection to endogenous growth theory, which emphasizes the strengthening of human capital and social institutions. This study, therefore, seeks to bridge this conceptual gap by analyzing the contributions of zakat and waqf through this theoretical framework. Employing a qualitative approach, this study analyzes secondary data from authoritative institutions, including BAZNAS, the Ministry of Religious Affairs, and BPS, using thematic content analysis. The findings reveal the dual function of these instruments: Zakat effectively addresses immediate consumption needs and provides microfinance support, while waqf focuses on creating productive assets for long-term welfare. Furthermore, our results underscore that the adoption of digital technology has been a critical catalyst, enhancing transparency, efficiency, and outreach. The primary contribution of this research is its positioning of Islamic philanthropy within the framework of modern economic growth theory, highlighting its relevance to achieving the Sustainable Development Goals (SDGs). It is acknowledged, however, that the study’s reliance on secondary qualitative data limits the ability to measure quantitative impacts at the micro-level.